Intestinal Microbiota in Patients with Chronic Heart Failure and Systolic Dysfunction - M. V. Fadeeva; A. V. Kudryavtseva; G. S. Krasnov; M. R. Skhirtladze; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To study the composition of the intestinal microbiota in patients with chronic heart failure (CHF), as well as a relationship between the features of the CHF clinical course and changes in the microbial composition of the colon.Materials and methods. The study included 60 heart failure patients with systolic dysfunction diagnosed according to the results of echocardiographic examination. The control group consisted of 20 patients comparable to the main group by gender, age and underlying diseases in the absence of CHF. In all patients, the severity of CHF symptoms was assessed using a clinical assessment scale. The levels of the N-terminal fragment of the cerebral natriuretic peptide (NT-proBNP) and C-reactive protein (CRP) were determined. Echocardiographic examination and, if indicated, Holter ECG monitoring were performed. The intestinal microbiota in stool samples was studied by sequencing the 16S gene of ribosomal RNA (rRNA).Results. In comparison with the control group, CHF patients showed a decrease in the relative content of Tenericutes (p = 0.02, Mann—Whitney test) and an increase in the proportion of Euryarchaeota (p = 0.02) and Firmicutes (p = 0.03). At the family level, an increase in the proportion of Methanobacteriaceae (p = 0.03) and a decrease in the proportion of Pseudomonadaceae (p = 0.01) and Moraxellaceae (p = 0.01) were noted. No dependence of the intestinal microflora composition on the functional class of heart failure was observed. However, a correlation was revealed between the relative number of certain bacterial families and the severity of impaired contractile function, the level of the inflammatory marker and the biochemical marker of heart failure.Conclusions. The obtained data indicate differences in the intestinal microbiota composition in patients with and without heart failure. A correlation between the number of some bacterial families and various laboratory and instrumental indicators assessed in heart failure patients was revealed. Further research into the effect of intestinal microbiota on the course of heart failure appears to be promising for improving treatment methods.